Sharpe vs Treynor: Strategies for evaluating stock portfolio performance on the Indonesian Stock Exchange - Thersia M M Da Silva; Petrus E de Rozari; Darwin Zebua; Efandri Agustian (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates whether the Sharpe Ratio and Treynor Ratio produce significantly different portfolio performance rankings in the Indonesian stock market. A quantitative research design was employed using a sample of 11 large-capitalization companies representing each IDX-IC sector listed on the Indonesia Stock Exchange during the 2020–2024 period. An optimal portfolio was constructed under a 0%–30% asset allocation constraint, and portfolio performance was assessed using the Sharpe Ratio and Treynor Ratio. Differences in portfolio rankings were examined through descriptive, comparative, and paired t-test analyses. The optimized portfolio generated an expected return of 74.60%, with a Sharpe Ratio of 5.60 and a Treynor Ratio of 0.0697. The paired t-test yielded a p-value of 0.331, indicating no statistically significant difference between the rankings produced by the two performance measures. These findings suggest that, for well-diversified portfolios in which unsystematic risk has been effectively diversified away, the Sharpe Ratio and Treynor Ratio provide comparable assessments of investment performance. This study extends the evidence on risk-adjusted portfolio evaluation in an emerging market context and provides practical implications for investors and portfolio managers in selecting appropriate performance measurement approaches. Keywords: Sharpe Ratio; Treynor Ratio; Portofolio Performance; Indonesian Stock Exchange